Society of Pediatric Psychology Workforce Survey: Updated Factors Related to Compensation. (18th February 2020) - Kichler, Jessica C; Valenzuela, Jessica; Barker, Dave; Noser, Amy E; Brosig, Cheryl L; Hilliard, Marisa E; Christidis, Peggy; Stamm, Karen E; Wysocki, Tim; Jelalian, Elissa
Abstract: Objective: The 2017 Society of Pediatric Psychology (SPP) Workforce Survey provides self-reported compensation by pediatric psychologists, identifies predictors of compensation, and establishes a better understanding of compensation within the context of gender and race/ethnicity minority status. Methods: SPP members who attended the SPP Annual Conference (SPPAC; April 2017) were invited to complete the survey at the conference through electronic tablets provided on-site by the Workforce Survey Committee. The survey was subsequently distributed online to SPP members who did not complete the survey at SPPAC. The statistical analyses used for this salary data employed flexible semi-parametric models, cross-validation, and prediction models for both the overall sample and academic rank subgroups. Results: Of 27 potential demographic and employment-related predictors from the 2017 SPP Workforce Survey, significant predictors of salary emerged within this sample: academic rank, time since obtaining doctoral degree, managing internal and external funds (of at least 50, 000), years in primary employment position, obtaining Fellowship status in the American Psychological Association (APA), and managing other employees (at least 10 people). Given low response rates for males and individuals who identify as belonging to racial and ethnic minority subgroups, only limited, exploratory results are reported for these subgroups. Conclusions: These findings suggest that not only is longevity in one's career important but managing funds/personnel and obtaining professional designations are also predictors of higher salaries for pediatric psychologists, in general. Specific implications of salary according to the psychologist's academic rank, gender, and racial/ethnicity group status are also explored.